OPERATIONAL MANAGEMENT ANALYSIS OF WASTE BANK "BERKAH" IN ENHANCING COMMUNITY-BASED WASTE MANAGEMENT EFFICIENCY IN MAKASSAR - Azwar Jayanegara B; Mahfudnurnajamuddin; Suriyanti (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the operational management system of Waste Bank "Berkah" in enhancing the efficiency of community-based waste management in Makassar, focusing on operational processes, efficiency indicators, and socioeconomic impacts. This research employs a qualitative case study approach. Data were collected through participant observation, in-depth interviews with 15 stakeholders (managers, customers, government officials, and partners), focus group discussions, and document analysis. The research was conducted from January to March 2025 at Waste Bank "Berkah" in Tamalanrea District, Makassar. Data analysis utilized thematic analysis with NVivo 12 software, ensuring validity through data triangulation and member checking. The study reveals that Waste Bank "Berkah" has implemented a structured operational management system comprising six main processes: collection, sorting, weighing, recording, processing, and marketing. Key performance indicators show significant improvements: waste processing time reduced by 53% (from 15 to 7 minutes per kilogram), sorting accuracy increased by 17% (from 75% to 92%), and monthly customer income increased by an average of IDR 300,000. The waste recovery rate reached 85%, contributing to circular economy implementation. This research provides empirical evidence of operational management practices in community-based waste banks, contributing to the literature on sustainable operations management and circular economy implementation in developing countries.